Spontaneous retroperitoneal hematoma mimicking retroperitoneal malignancy in a pregnant woman - Özdemir, Serdar; Sönmez, Ertan (Journal of Surgery and Medicine, 2020)
Spontaneous retroperitoneal hematomas can cause maternal and fetal complications during pregnancy. A female patient with 10 weeks’ gestation was referred to our clinic with back pain by her gynecologist for retroperitoneal mass excision and termination of pregnancy, due to the retroperitoneal malignancy seen on ultrasonography. MRI revealed a 90x110 mm retroperitoneal hematoma adjacent to the posterior of the left kidney. The patient was followed conservatively for 7 days and discharged without any fatal or maternal complications. We recommend that advanced imaging methods should be preferred in selected cases.